Antifungal activity of fluconazole-loaded natural rubber latex against Candida albicans - Yonashiro Marcelino, Mônica [UNESP]; Azevedo Borges, Felipe [UNESP]; Martins Costa, Ana Flávia [UNESP]; De Lacorte Singulani, Junya [UNESP]; Ribeiro, Nathan Vinícius [UNESP]; Barcelos Costa-Orlandi, Caroline [UNESP]; Garms, Bruna Cambraia [UNESP]; Soares Mendes-Giannini, Maria José [UNESP]; Herculano, Rondinelli Donizetti [UNESP]; Fusco-Almeida, Ana Marisa [UNESP] (Taylor & Francis, 2018)
Aim: This work aimed to produce a membrane based on fluconazole-loaded natural rubber latex (NRL), and study their interaction, drug release and antifungal susceptibility against Candida albicans. Materials & methods: Fluconazole-loaded NRL membrane was obtained by casting method. Results: The Fourier Transform Infrared Spectroscopy showed no modifications either in NRL or fluconazole after the incorporation. Mechanical test presented low Young's modulus and high strain, indicating the membranes have sufficient elasticity for biomedical application. The bio-membrane was able to release the drug and inhibit the growth of C. albicans as demonstrated by disk diffusion and macrodilution assays. Conclusion: The biomembrane was able to release fluconazole and inhibit the growth of C. albicans, representing a promising biomaterial for skin application.
Keywords: Candida albicans; fluconazole; natural rubber latex (NRL)